INKUBATOR IDE BERBASIS DESIGN THINKING UNTUK KEPEMIMPINAN PEMUDA KARANG TARUNA DI KOMPLEK SKUADRON HALIM PERDANA KUSUMA - Ayi Ahmid Nurdin; Sugeng Prayetno; Hendra Permadi; Rhoma Iskandar; Winna Sari Kusumaningtyas; Az-Zahraadita Bahira Ramadina; Maya Purnama Siddhi; Iis Kurniawati (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Strengthening youth leadership is a strategic aspect of urban community development in addressing complex and dynamic social challenges. However, youth potential is often not optimally developed due to the absence of a systematic and sustainable idea development platform. This community service program aims to strengthen youth leadership and creativity through the establishment of the Camp GenLead Creative Lab as a Design Thinking–based idea incubator. The partner of this program was a youth organization operating in an urban community context. The implementation method applied a participatory approach through five stages of Design Thinking, namely empathize, define, ideate, prototype, and test. Data were collected through field observations, focus group discussions, documentation, and pre–post activity evaluations. The results indicate a significant improvement in youth competencies, with the average score increasing from 2.8 to 3.7 on a four-point scale. In addition, the program produced several social innovation prototypes and successfully formed a sustainable youth idea incubation platform. These findings demonstrate that a Design Thinking–based idea incubator plays an important role in strengthening youth leadership and fostering sustainable social innovation in urban communities.